2022
DOI: 10.3390/nu14071377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moderate Wine Consumption on Oxidative Stress Markers in Coronary Heart Disease Patients

Abstract: Evidence from research studies reports that wine consumption is associated with lower cardiovascular disease risk, partly through the amelioration of oxidative stress. The aim of the present study was to examine the effect of regular light to moderate wine consumption from coronary heart disease (CHD) patients compared to the effect induced by alcohol intake without the presence of wine microconstituents, on oxidation-induced macromolecular damage as well as on endogenous antioxidant enzyme activity. A randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Legumes (an essential component of MeDi score) containing procyanidin, with high contents of magnesium and low glycemic index, is associated with the reduced oxidative stress [34]. Moderate wine consumption exerts antioxidant actions and is associated with reduced risk of PD [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Legumes (an essential component of MeDi score) containing procyanidin, with high contents of magnesium and low glycemic index, is associated with the reduced oxidative stress [34]. Moderate wine consumption exerts antioxidant actions and is associated with reduced risk of PD [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies did not demonstrate beneficial effects of RW consumption on lipid metabolism [27,100]. The ingestion of DRW, but not RW, decreased circulating F2-isoprostanes, a prostaglandin-like compound formed from the free-radical-mediated oxidation of arachidonic acid [13].…”
Section: Lipid Profile and Homocysteine Levelsmentioning
confidence: 93%
“…RW's antioxidants also suppress the post-prandial activation of NF-κB, an oxidative-stress-related transcription factor involved in the regulation of inflammatory responses [17,70]. Similarly, oxidized guanine species and protein carbonyl levels were significantly decreased in the RW group in CAD patients [100]. Importantly, it is well established that the beneficial effects observed after RW consumption, in terms of the increased activity of antioxidant enzymes, are not due to the alcohol content in wine, but to the polyphenolic composition.…”
Section: Antioxidant Statusmentioning
confidence: 95%
“…Therefore, oxidative stress plays a key role in the pathophysiological processes that underlie liver damage related to excessive alcohol consumption [ 9 , 10 ]. However, the results of several studies associate regular consumption of wine in moderate amounts with beneficial cardiovascular effects and a low incidence of deaths from atherosclerosis and coronary heart disease, effects related to increased levels of high-density lipoprotein (HDL), but which have not always been confirmed in the case of white wine [ 2 , 6 , 12 , 13 , 14 , 15 ]. Despite numerous studies referring to the beneficial effects of red wine, Radeka et al, have shown that white wines, not just red wines, have produced a decrease in systolic and diastolic blood pressure, total cholesterol and LDL levels, and an increase in HDL levels and serotonin and dopamine levels, following regular consumption for six weeks [ 16 ].…”
Section: Introductionmentioning
confidence: 99%